Novel Molecular Therapeutics Targeting Signaling Pathway to Control Hepatitis B Viral Infection - Yan, Yan; Qiu, Yuanwang; Davgadorj, Chantsalmaa; Zheng, Chunfu (Frontiers in Cellular and Infection Microbiology, 2022)
Numerous canonical cellular signaling pathways modulate hepatitis B virus (HBV) replication. HBV genome products are known to play a significant role in regulating these cellular pathways for the liver’s viral-related pathology and physiology and have been identified as the main factor in hepatocarcinogenesis. Signaling changes during viral replication ultimately affect cellular persistence, multiplication, migration, genome instability, and genome damage, leading to proliferation, evasion of apoptosis, block of differentiation, and immortality. Recent studies have documented that numerous signaling pathway agonists or inhibitors play an important role in reducing HBV replication in vitro and in vivo, and some have been used in phase I or phase II clinical trials. These optional agents as molecular therapeutics target cellular pathways that could limit the replication and transcription of HBV or inhibit the secretion of the small surface antigen of HBV in a signaling-independent manner. As principle-based available information, a combined strategy including antiviral therapy and immunomodulation will be needed to control HBV infection effectively. In this review, we summarize recent findings on interventions of molecular regulators in viral replication and the interactions of HBV proteins with the components of the various targeting cellular pathways, which may assist in designing novel agents to modulate signaling pathways to prevent HBV replication or carcinogenesis.